Bulleyaconitine A Exerts Antianxiety and Antivisceral Hypersensitivity Effects - Huang, Sheng-Nan; Yang, BeiBei; Ma, Le; Huang, Lan-Ting; Ju, Pei-Jun; Wei, Jinbao; Ali, Usman; Wang, Yong-Xiang; Chen, Jinghong (Frontiers in Pharmacology, 2020)
Visceral pain is one of the leading causes for abdominal pain in gastroenterological diseases and is still hard to treat effectively. Bulleyaconitine A (BAA) is an aconitine analog and has been used for the treatment of pain. Our previous work suggested that BAA exerted analgesic effects on neuropathic pain through stimulating the expression of dynorphin A in spinal microglia. Here, we investigated the inhibitory effect of BAA on visceral pain and examined whether the expression of dynorphin A in spinal microglia was responsible for its effects. We found that BAA produced significant antivisceral pain effect induced by acetic acid through stimulating dynorphin A expression in spinal microglia. In addition, anxiety and chronic visceral pain are highly prevalent comorbid conditions in clinical research, which is still a problem to be solved. We also aimed to evaluate the effects of BAA on anxiety. A comorbidity model with characteristics of both chronic visceral pain and anxiety was developed by colorectal injection of 2,4,6-trinitrobenzene sulfonic acid and the induction of heterotypic intermittent chronic stress protocol. In comorbid animals, BAA exerted great antianxiety effects. Meanwhile, the antianxiety mechanism of BAA was different with the antivisceral pain mechanism of BAA. In conclusion, our study demonstrated, for the first time, that BAA exerted marked antivisceral pain and antianxiety effects, which expands the analgesic spectrum and clinical application of BAA. Furthermore, it also it provides a better guidance for the clinical use of BAA.